Penerapan Layanan Hak Tanggungan Secara Elektronik Dalam Praktik Pemberian Hak Tanggungan Kepada Kreditor - Anggrahini Anggrahini; Heru Kuswanto (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
The granting and imposition of mortgage rights for granting APHT by the PPAT in front of the parties then submitting the APHT to the land office based on the obligations provided by the Mortgage Law, PP on Land Registration and PP on PPAT Position Regulations where the PPAT is required to submit the original sheet of the second APHT and its supporting papers to the land office in physical form, but after the entry into force of the ATR/BPN Ministerial Regulation concerning electronic HT, it stipulates that the intended submission can be made electronically. Based on this, the author wants to examine the status of land registration of mortgage rights through electronic means and the responsibilities of the PPAT. The writing method uses normative juridical research and based on the results of the research it is known that submission of APHT which is no longer through submission of original files brings legal consequences for the PPAT namely the PPAT is responsible for the existence and integrity of all APHT documents stored in it.